Enhanced oral absorption of salmon calcitonin-encapsulated PLGA nanoparticles by adding organic substances - Jung, Tae-Sung; Kwon, Byung-Soo; Lee, Hea-Eun; Kim, Ah-Young; Lee, Min-Jeong; Park, Cho-Rong; Kang, Ho-Kyung; Kim, Young-Deug; Lee, Sang-Kil; Kang, Jae-Seon; Choi, Guang-Jin (The Korean journal of chemical engineering, 2009)
Two organic compounds with potential absorption enhancing effects, bile acids and transferrin, were examined by the gastro-intestinal (GI) absorption of therapeutic salmon calcitonin (sCT) as encapsulated by poly(lactide-co-glycolide) (PLGA) for the treatment of osteoporosis. The sCT-loaded PLGA nanocapsules were prepared by O/W emulsification approach. Either additive of a designated content was mixed with sCT dissolved in methanol. For bile acids, their content (0–7.5 mg to sCT 6 mg) was observed to have a substantial effect both on the emulsification process and the encapsulation efficiency. When 1.5 mg of bile acids was added, sCT-loaded PLGA nanocapsules of about 700 nm in diameter and with a fairly high encapsulation efficiency greater than 35% were produced. Accordingly, this formulation gave the most significant hypocalcemic effect in an in vivo experiment with SD rats. On the other hand, a too high bile acids loading resulted in a poor encapsulation efficiency of less than 7%. Two principal roles of bile acids were proposed: emulsifying agent and absorption enhancer. Transferrin, a human glycoprotein of 80 kDa molecular weight, turned out to have potential as absorption enhancer as well.